2001
DOI: 10.1096/fj.00-0020com
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones (PPARγ agonists) but not PPAR α agonists increase IRS‐2 gene expression in 3T3‐L1 and human adipocytes1

Abstract: Thiazolidinediones (TZD) improve insulin sensitivity in human as well as in different animal models of insulin resistance and Type 2 diabetes. However, no clear link to the insulin signaling events has been identified. Using differentiated 3T3-L1 adipocytes, we found that TZD rapidly and markedly increased IRS-2 gene expression. This effect was specific for PPARgamma agonists and was not seen with PPARalpha agonists. It was rapidly induced (within 4 h) and maintained throughout the observation period of 48 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 29 publications
5
81
2
3
Order By: Relevance
“…In 3T3-L1 adipocytes, thiazolidinediones induced expression of the IRS2 gene through PPARg activation (Smith et al 2001). In our hands we could not find any activating effects of rosiglitazone using our IRS2 promoter reporter plasmids (data not shown).…”
Section: Effects Of Glucose and Pparg On Irs2 Promotermentioning
confidence: 62%
See 1 more Smart Citation
“…In 3T3-L1 adipocytes, thiazolidinediones induced expression of the IRS2 gene through PPARg activation (Smith et al 2001). In our hands we could not find any activating effects of rosiglitazone using our IRS2 promoter reporter plasmids (data not shown).…”
Section: Effects Of Glucose and Pparg On Irs2 Promotermentioning
confidence: 62%
“…6A, we were not able to induce IRS2 promoter activity in HepG2 cells with increasing amounts of glucose. Thiazolidinediones, which promote insulin sensitivity in humans by PPARg activation increased IRS2 gene expression in 3T3-L1 cells and human adipocytes (Smith et al 2001). Moreover, pioglitazone induced IRS1 but not IRS2 expression in muscle (Hammarstedt & Smith 2003).…”
Section: Discussionmentioning
confidence: 96%
“…We are currently investigating the effects of other activators of PPARα to confirm its implication in muscle cells. It has also been demonstrated that IRS-2 [42] and p85α PI 3-kinase [17] gene expression can be induced by activation of PPARγ in human adipocytes and that this effect leads to improved insulin signalling [17]. The ligands of PPARγ were inefficient in myotubes, probably due to the low expression level of this nuclear receptor in muscle [18].…”
Section: Discussionmentioning
confidence: 99%
“…Pierce, NCI, National Institutes of Health) and the IRS-1 probe of a PCR-amplified 409-bp fragment as described (41). Protein and RNA blots were scanned using a Personal Densitometer (Amersham Biosciences) and analyzed using ImageQuant software provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%